Desenvolvimento de sistemas microparticulados planejados para a liberação oral do risedronato de sódio - Velasquez, Aline de Arce (2012)
This work aimed the development of polymeric microparticles containing sodium risedronate from Eudragit S100® (MP-EUD) and the blend, Eudragit S100® and Pullulan (MP-EUD-PUL), through spray-drying technique. MP-EUD were obtained with a yield of 54%, encapsulation efficiency of 90%, average particle size of 3.3 μm and presented spherical shape. The moisture content was 8% and the Carr Index and Hausner Factor indicated poor flowability. At pH 1.2 23% risedronate sodium was released after 120 min, while the drug at pH 6.8 took 90 min to reach 99.5%. The mathematical modeling showed that the drug release followed first order kinetics and Fickian diffusion. Tablets prepared by direct compression of MP-EUD using different polyvinylpirrolidone concentrations showed low weight variation, thickness and drug content. Furthermore, they presented low friability and adequate hardness. In vitro studies indicated that no more than 16% of the drug was released in 120 min at pH 1.2. At pH 6.8 the risedronate release was prolonged for 270 min and folowed first order kinetics and Fickian diffusion. Concerning MP-EUD-PUL, three proportions of Eudragit S100® and Pullulan (1:2, 1:1 and 2:1) were studied. Microparticles were obtained with yields ranging from 31% to 42%, encapsulation efficiencies close to 100%, moisture contents lower than 11%, mean particle size in the range of 2.9 μm - 4.8 μm and narrow size distributions. Carr index and Hausner ratio indicated poor flowability. In gastric simulated fluid the microparticles prepared with the highest amount of Eudragit S100® showed the best gastroresistance. In intestinal simulated fluid blend microparticles were able to prolong the drug release. MP-EUD-PUL 2:1 were compressed into tablets with or without a binder. Both tableted microparticles could be obtained with acceptable average weights, drug content close to 100%, sufficient hardness and low friability. In vitro studies showed that tablets maintained the gastroresistance observed for untableted microparticles and were also able to prolong risedronate release. Finally, the formulations developed in this study represent promising alternatives for sodium risedronate oral delivery.